Performance of Eucalyptus Species and Provenances in South-West Punjab - Dogra, A. S.; Sharma, S. C. (Indian Forester, 2005)
A trial comprising 16 accessions of Eucalyptus species and provenances introduced from different locations in Australia was established in Ferozepur Forest Division of Punjab in 1982 to evaluate differences in growth and yield. Data on various growth parameters were collected from the experimental plot up to the age of 8.5 years. Basal area ranged from 12.6 to 29.5 m2 ha-1 with the Laura area provenance of Eucalyptus tereticornis having the highest value. Statistical analyses showed significant differences between provenances in growth parameters assessed. Mean annual increment, measured in terms of product of diameter square and height (D2H), varied from 19.7 to 68.8 m3 ha-1years and was again the highest in E.tereticornis, Laura area source, which exhibited superiority over control. It is recommended that E.tereticornis of Laura Area and four other species/provenances including control, which were not significantly inferior to it, may be used as the source for tree improvement.